Bilingualism and Language Disorders in Early Childhood: An Exploratory Case Study on Toddlers - Rizky Anugrah Putra; Syamsuddin Syamsuddin Syamsuddin; Suparni Suparni; Usman Pakaya (Yayasan Kyadiren, 2025)
In early childhood, inadequate parenting and excessive screen exposure are often linked to delays in first language acquisition. A bilingual environment is also suspected to contribute to these challenges. If left unaddressed, such factors may lead to language development issues, including speech delay and symptoms of autism. This study uses an exploratory case study approach involving two children, aged 4 and 5, raised in bilingual households. Data were collected through language behavior observations and interviews with their parents. Findings indicate that both children exhibited speech delays and signs within the autism spectrum. These difficulties were associated with inconsistent parenting and the high linguistic complexity from multiple languages used at home, which hindered optimal language development. Additionally, comorbid health issues such as dental caries and early tooth extraction negatively impacted their speech ability. The study emphasizes the importance of consistent, responsive parenting in supporting first language development in bilingual environments.